AN ANATOMICAL REVIEW OF THE HEART'S LEFT ATRIAL APPENDAGE - A.A. IAKIMOV; A.R. SAYFULINA; A.A. GAPONOV (Паёми Сино)
Objective: The objective of this study is to systematize the information available in the literature regarding the normal anatomy of the left atrial appendage (LAA) in humans and to identify the anatomical features that contribute to high risk for cardiogenic complications, such as atrial fibrillation, LAA thrombosis, and thromboembolic strokes. An information search was conducted on journal articles from 2014 to 2024 using PubMed with the keywords "left atrial auricle", "left atrial appendage", and "anatomy", as well as in an eLibrary with the keywords "anatomy of the left auricle of the heart" and "the left atrial appendage". The inclusion criteria focused on review or original articles specifically addressing the anatomy of the LAA. Articles related to a) heart anatomy in children or fetuses, b) animal anatomy, c) clinical aspects, d) heart anomalies, and e) methodological issues were excluded from consideration. Two primary approaches exist for describing the LAA shapes: one is based on the number of lobes. At the same time, the other relies on subjective comparisons with arbitrary objects. The most common classification under the subjective approach, as proposed by Wang Y et al (2010), identifies LAA with shapes likened to a "chicken wing", a "cactus", a "cauliflower", or a "windsock". However, no studies were found that examined the shape of the LAA using objective criteria. This article examines both the external and internal aspects of the LAA, including its volume, ostium (orifice) size, topography, and internal wall relief. In patients with atrial fibrillation (AF) complicated by LAA thrombosis or a history of stroke, LAAs are typically multilobed, take on a shape distinct from the "chicken wing" (often resembling "cauliflower" or "arrowhead"), and exhibit extensive trabeculations and an oval orifice shape. The volume of these LAAs is 1.4 to 1.7 times greater than normal, with a volume exceeding 9.99 ml being considered a predictor of recurrent AF. The formation of a thrombus in the LAA is linked to an increase in the depth and area of the LAA. However, there is currently no data available regarding the impact of AF, LAA thrombosis, or stroke on the external dimensions and topography of the LAA.